Functional and Sectoral Division of Labour within Central and Eastern European Countries: Evidence from Greenfield FDI - Teodora Dogaru; Martijn Burger; Bas Karreman; Frank van Oort (Tinbergen Institute, 2014)
In this paper, we analyse the sectoral and functional division of labour in Central and Eastern European (CEE) regions within the convergence debate. By analysing the investment decisions of multinational corporations in 49 NUTS-2 regions across 6 European CEE countries (Poland, Czech Republic, Slovakia, Hungary, Romania, and Bulgaria), we show that capital city regions not only receive more greenfield FDI but also attract a larger variety of investments in terms of sectors and functions. Capital cities are more likely to host higher-end sectors and functions, which provides an explanation for the existing regional disparities within CEE countries. These results highlight the importance of functional and sectoral divisions of labour in the view of regional profiling and contribute to the recent EU Cohesion Policy debate.
Keywords: F23; R12; R58; 330; regional disparities; Central and Eastern Europe; greenfield FDI